Techniques to Reduce Capacitor Voltage Ripples in Multilevel Inverters - Shivam Prakash Gautam; Manik Jalhotra; Atif Iqbal; Lalit Kumar Sahu; Mano Ranjan Kumar; Meena Malik; Shima Sadaf (IEEE Access, 2023)
Reducing ripples on the capacitor voltage has two benefits: improved output waveform quality and accurate converter size. During the generation of a given output voltage level, the factor “Inherent Redundant Paths (IRPs)” has a considerable impact on the characteristics of multilevel inverter design. The consistent distribution of power loss derives from the Active Neutral Point-Clamed Inverter’s intrinsic redundant route at zero-voltage level generation. Even though it has been claimed that adding intrinsically redundant routes might give fault-tolerance capabilities to MLI topologies, the utilization of these pathways at intermediate voltage levels has not yet been studied. Based on this, the current research provides a unique charging and discharging technique is known as the alternating charging and discharging approach, which reduces capacitor voltage ripple. In addition, the suggested technique permits the inherent voltage balancing of capacitors without the need for supplemental components. The suggested alternative charging and discharging approach is implemented under both healthy and varied switch failure circumstances. In a laboratory prototype, the efficacy of the suggested alternative charging and discharging technique has been empirically tested.